Development Of Religious Behavior In Early Childhood - Trimuliana, Ifina; Hapidin, Hapidin; Supena , Asep (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Teachers have an important role in education, in fact their role is not just to transfer knowledge, but also to play a role in the process of developing religious behavior so that children grow into religious individuals. This research aims to determine the role of teachers in developing the religious behavior of children aged 5-6 years using a qualitative approach with the case study method. The research results found that the teacher's role consists of: 1) Pedagogy, related to the teacher's methods/strategies during the learning process, by applying various interesting learning methods and also special methods provided outside the learning process such as familiarization and collaboration with parents. 2) Understanding, namely having an understanding/view of the importance of religious behavior and the impact on children in the future when religious behavior is not strong in the child. 3) Facilities, providing supporting facilities including facilities and infrastructure at schools, such as places of worship, and various educational games